Optimalisasi Upaya Guru Bimbingan dan Konseling dalam Meningkatkan Kedisiplinan Peserta Didik di Madrasah Tsanawiyah Negeri Kota Palopo - Taqwa; Arwan Wiratman; Alimuddin; Hisban Thaha; Tasdin Tahrim; Muh. Ilham Setyawan (edujavare, 2025)
This research aims to determine the efforts of guidance and counseling teachers in improving student discipline at the State Tsanawiyah Madrasah Palopo City, to determine the level of discipline at the State Tsanawiyah Madrasah Palopo City and to find out what factors influence student discipline at the State Tsanawiyah Madrasah Palopo City. The type of research used is descriptive qualitative. The subjects of this research were school principals, guidance and counseling teachers, and students. Research data was obtained through interviews, observation and documentation studies. The data analysis techniques use data reduction, data presentation, and drawing conclusions. The results of this research show that; (1) The efforts of guidance and counseling teachers to improve the discipline of students at Madrasah Tsanawiyah Negeri Palopo City are related to guidance and counseling functions such as understanding functions, preventive functions, development functions, healing functions, adjustment functions, improvement functions, facilitation functions, maintenance function (2) The level of discipline at the State Madrasah Tsanawiyah Palopo City has increased sufficiently or is disciplined enough. This is indicated by indicators of discipline that have been implemented such as attendance, paying attention to the teacher when explaining lessons, carrying out assigned tasks, bringing study equipment, utilizing time. free time or rest to study and discuss or ask friends about lessons that are not well understood (3) Factors that influence the discipline of students at the State Madrasah Tsanawiyah Palopo City, namely the influence of peers, family environment, and the influence of technology.